Lady Macbeth's daughter - Klein, Lisa M. (Bloomsbury, 2010)
Ambitious Lady Macbeth tries to win the throne of Scotland for her husband while her banished daughter Albia, who was raised by three weird sisters, falls in love, learns of her parentage, and seeks to free Scotland from tyranny
Keywords: Gruoch / Queen, consort of Macbeth, King of Scotland / Juvenile fiction; Macbeth / King of Scotland / active 11th century / Juvenile fiction; Gruoch / Queen, consort of Macbeth, King of Scotland / Fiction; Macbeth / King of Scotland / active 11th century / Fiction; Kings, queens, rulers, etc / Juvenile fiction; People with disabilities / Fiction; Witchcraft / Fiction; Murder / Fiction; Geschichte; Scotland / History / To 1057 / Fiction; Schottland; Jugendbuch